PENGAJARAN MEMBACA PADA ANAK USIA DINI TUNAGRAHITA RINGAN DI SEKOLAH LUAR BIASA EMMANUEL MANADO - PUTRI, NI LUH (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
This research aim to know about difficulties of the mild mentally impaired children in reading and the causes of reading difficulties. This research design is descriptive and qualitative case study. Based on data analysis result, research outcome shows that: (1) Difficulties of reading in a mentally mild impaired child include: Difficulties of pronouncement, fluency (repetitiveness), perception, concentration, concern, recollection, differentiation of recollecting word having been read and word or not yet having been read, differentiation of recollecting line having been read or not yet having been read, understanding, motorics (2) Causes of the reading difficulties in a mentally mild impaired child include a) physical causes: malfunction or anomaly of speech device, motoric obstacle. b). auses of Mentality and Psychology : inaccurateness if perception, inability for concentration, his or her recollection is less, differentiation in recollecting word having been read and word not yet having been read is vague, differentiation in recollecting the line having been read and not yet having been read is vague, emotional impediment, low intelligence.Keywords: teaching reading, early childhood, mild mentally impaired